Linking growth mode to lengths of single-walled carbon nanotubes. (March 2017) - He, Maoshuai; Magnin, Yann; Amara, Hakim; Jiang, Hua; Cui, Hongzhi; Fossard, Frédéric; Castan, Alice; Kauppinen, Esko; Loiseau, Annick; Bichara, Christophe
Abstract: Elucidating the key factors that determine the lengths of single-walled carbon nanotubes (SWCNTs) is of great importance for understanding the origin of chiral selectivity. We use transmission electron microscopy to thoroughly investigate as-grown SWCNTs. The lengths and growth modes of SWCNTs were decided by bright-field imaging. Their respective chiral angles were calculated on the basis of nanobeam diffraction patterns. Systematic investigations reveal that there is no correlation between the SWCNT length and its chiral angle. Instead, it shows that SWCNT lengths depend more on their growth mode, i.e. the link between SWCNT and its seeding catalyst particle. Atomistic computer simulations demonstrate that low carbon fractions in the catalyst lead to so-called tangential growth, with a partial wetting of the metal in the tube, where metal catalyst tends to be deactivated by graphite layer encapsulation and results in short SWCNTs. In contrast, a high carbon concentration inside metal particle favors perpendicular growth modes, where only the tube lip is in contact with the catalyst. Catalysts adopting perpendicular mode could have a longer lifetime, thus catalyze the growth of long SWCNTs. Finally, the carbon concentration related growth mode was applied to interpret diverse SWCNT growth results. Graphical abstract: